Gene-expression programming for scour around spur dike - Tripathi R.P.; Pandey K. (My University, 2025)
Spur dikes are hydraulic structures construct in the river or channel and help for saving the bank from erosion, deepen the upstream channel and the habitat present on the dyke of the river. Due to the importance of river dike as a natural habitat for microorganisms, researchers are attracted to the scour formed around the spur dike; however, the straight channel spur dike is studied most in current days, along with the curved channel or bends. The current paper deals with expanding GP. The GEP is an alternative approach in the way of modelling, which predicts the maximum scour depth. The introduced GEP model may apply to various boundaries with the part-full flow, and the approach gives excellent results compared to pre-existing data. © 2023 Inderscience Enterprises Ltd.